On Conan Doyle, or, The whole art of storytelling - Dirda, Michael (Writers on writers., 2012)
A passionate lifelong fan of the Sherlock Holmes adventures, Pulitzer Prize-winning critic Michael Dirda is a member of The Baker Street Irregulars--the most famous and romantic of all Sherlockian groups. Combining memoir and appreciation, On Conan Doyle is a highly engaging personal introduction to Holmes's creator, as well as a rare insider's account of the curiously delightful activities and playful scholarship of The Baker Street Irregulars. Because Arthur Conan Doyle wrote far more than the mysteries involving Holmes, this book also introduces readers to the author's lesser-known non-fiction and fiction works.